If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2(x + -6) = 2(x + -5) + 7 Reorder the terms: 7x + -2(-6 + x) = 2(x + -5) + 7 7x + (-6 * -2 + x * -2) = 2(x + -5) + 7 7x + (12 + -2x) = 2(x + -5) + 7 Reorder the terms: 12 + 7x + -2x = 2(x + -5) + 7 Combine like terms: 7x + -2x = 5x 12 + 5x = 2(x + -5) + 7 Reorder the terms: 12 + 5x = 2(-5 + x) + 7 12 + 5x = (-5 * 2 + x * 2) + 7 12 + 5x = (-10 + 2x) + 7 Reorder the terms: 12 + 5x = -10 + 7 + 2x Combine like terms: -10 + 7 = -3 12 + 5x = -3 + 2x Solving 12 + 5x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 5x + -2x = -3 + 2x + -2x Combine like terms: 5x + -2x = 3x 12 + 3x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 3x = -3 + 0 12 + 3x = -3 Add '-12' to each side of the equation. 12 + -12 + 3x = -3 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = -3 + -12 3x = -3 + -12 Combine like terms: -3 + -12 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| 5x/16=5/32 | | 95x-31=x-(-51) | | 3(6x+9)=117 | | (4i-5)(6-7i)= | | -4/3a=8 | | 4x*2x+10= | | -24-n=32 | | (5x^2-3y)(x^2-y)=0 | | x+(x+22)+x+(x+22)=720 | | 6x+1=3x+-11 | | 3x-2=25+6x | | -4=m/20-5 | | 81-42=w | | -5(t-1)+8t=5t-4 | | 137-w=274 | | 9j-9=9+3j+9j | | 81-42= | | 3(2x-3)=8x-5 | | 27z-66=z-(-60) | | 6(x-1)+5=3x+3(-1+x) | | 27z-60=z-(-60) | | t/5=16 | | 4x-y+11=0 | | 7x+7-9x=13-15x+13x-6 | | 7-p+5p=9 | | W(3w+2)=456 | | 1.5x+3.5x-2=18 | | 30x+25y=280 | | -11z-50=z-(-8) | | 3=d | | 70+60= | | 4y=y+-20 |